Thermostability and free radical scavenging activity of Annona muricata(L.) leaf extract in antiaging cream - Alvin Aldo; Gabriela Eugresya; Mediana Hadiwidjaja; Christina Avanti (Universitas Ahmad Dahlan, 2019)
Annona muricata is an Indonesian medicinal plant commonly used as an anticancer agent. The finding of its strong antioxidant activity leads to the development of cosmetic products, particularly as antiaging cream. Formulation may influence thermostability and free radical scavenging activity of A.muricata leaf extract. The purpose of this study was to investigate the thermostability and free radical scavenging activity of A.muricata leaf extract incorporated in Gattefosse Skin Cashmere cream. Accelerated stability study utilizing climatic chamber at a temperature of 40ºC ± 2ºC and relative humidity of 75% ± 5% for 20 days of storage was used to evaluate thermostability. 1,1-diphenyl-2-picrylhydrazil (DPPH) using spectrophotometer was used for free radical scavenging activity test. The result from physical properties including appearance of antiaging cream, pH, viscosity and rheological properties of each formula showed that all of the formulas were stable at a temperature of 40ºC ± 2ºC and relative humidity of 75% ± 5% for 20 days. Free radical scavenging activity using DPPH showed high antioxidant activities from the A.muricata leaf extract in the Gattefosse Skin Cashmere cream. We concluded that A. muricata leaf extract could be developed into natural antiaging cosmetic product.